Distribution methods of ostomy and incontinence aids in the Italian healthcare setting: an evaluation questionnaire and social burden of direct distribution - Filippo Rumi; Francesca Orsini; Vincenzo Falabella; Pier Raffaele Spena; Americo Cicchetti (Global & Regional Health Technology Assessment, 2022)
Background: The distribution of ostomy and incontinence devices takes place through different modalities according to the regional provisions in force. A first possibility is represented by direct distribution by the local health authorities. A second possibility consists of indirect distribution through affiliated retailers, typically pharmacies and authorized retailers of medical devices. A third form of distribution concerns home distribution.